Walking with light and the discontinuous experience of urban change. Issue 2 (21st December 2020) - Ebbensgaard, Casper Laing; Edensor, Tim
Abstract : This paper is concerned with the affective power of light, darkness, and illumination and their role in exposing and obscuring processes of rapid urban change. Little academic attention has focused on how lighting informs multiple, overlapping, and intersecting urban temporalities and mediates our experience of an ever‐changing city. This paper foregrounds a walk through the illuminated city at night as an epistemic opportunity to develop an embodied account of material and temporal change in ways that disrupt the aesthetic organisation of the sensible world at night. By detailing the discontinuous experience of walking through differently lit spaces, the paper develops novel ways of conceptualising the experience of urban change that unsettle common understandings of subjectivity, temporality, and the city. The paper draws on a single night's walk from Canning Town to Canary Wharf in east London – an area that has recently undergone rapid change, including the erection of enclaves of high‐rise development. By accentuating the shared experiences of walking with light, we reveal the affective capacities of light and dark to conceal and expose wider material, embodied, and temporal urban changes but also how we might challenge the organisation of the nocturnal field of the sensible. Abstract : This paper is concerned with the affective power of light, darkness, and illumination and their role in exposing and obscuring processes of rapid urban change. By detailing the discontinuous experience of walking through differently lit spaces, the paper develops novel ways of conceptualising the experience that unsettle common understandings of subjectivity, temporality, and the city. The paper draws on a single night's walk from Canning Town to Canary Wharf in east London.